Phase- and morphology-controlled synthesis of tunable plasmonic MoO3-x nanomaterials for ultrasensitive surface-enhanced raman spectroscopy detection - Patil, Manoj Krishnat; Gaikwad, Supriya Hanmant; Mukherjee, Shatabdi Porel (Journal of Physical Chemistry C, 2020)
The enhancement of the surface-enhanced Raman scattering (SERS) property of the plasmonic metal oxide semiconductor nanostructures by controlling their phase, shape, size, and oxygen vacancy to detect trace amounts of organics is of significant interest. In this study, a simple surfactant-free hydrothermal strategy was proposed to fabricate crystalline h-MoO3-x and alpha-MoO3-x nanomaterials with tunable plasmonic properties. Herein, the crystal phase, morphology, and oxygen vacancy of MoO3-x nanostructures were precisely controlled under suitable synthetic conditions. The plasmonic properties of the as-synthesized h-MoO3-x and alpha-MoO3-x micro-/nanostructures were controlled by adjusting the residual volume in the autoclaving chamber. In addition, the plasmonic MoO3-x exhibited SERS activity with a detection limit as low as 1.0 x 10(-9) M and the maximum enhancement factor (EF) up to 6.99 x 10(5) for h-MoO3-x, while for alpha-MoO3-x, the detection limit was 1.0 x 10(-7) M with the corresponding EF up to 8.51 x 10(3), comparable with plasmonic noble metal nanomaterials without a ``hot spot''.

2D MoO2/N-Doped-carbon nanosheets as SERS tweezers: a non-noble metal reusable substrate for selective organic dye detection - Gaikwad, Supriya Hanmant; Mukherjee, Shatabdi Porel (ACS Applied Nano Materials, 2021)
The design and synthesis of a highly sensitive and exceptionally selective surface-enhanced Raman scattering (SERS) substrate with an excellent reusable property are of significant interest because of its vast prospective application in actual and complicated detection environments. Here, a simple synthesis strategy was presented to fabricate crystalline two-dimensional (2D) MoO2/N-doped-carbon nanosheets with the plasmonic property. The morphology, crystal phase, and surface property of MoO2 nanomaterials (NMs) were specifically controlled under suitable reaction conditions. In addition, the plasmonic MoO2/N-doped-carbon NM exhibited a SERS maximum enhancement factor up to 1.38 × 104 with a detection limit as low as 1.0 × 10–6 M. More importantly, the as-synthesized nanocomposite shows high selectivity as a “SERS Tweezer” toward methylene blue (MB) in binary and ternary mixed interfering analyte solutions, preserving detection sensitivity toward MB for three cycles via an “elect-and-eliminate” approach. This strategy will be helpful to design other plasmonic semiconductor NMs for successful tangible applications of selective SERS sensing for trace impurity detections in real and complex environments.

Synthesis of 2D MoO3-x/N-doped-carbon nanocomposites via in situ carbonization of layered (NH4)Mo3O9-(NH4)(2)Mo4O13-organic hybrid nanomaterials for exceptionally efficient adsorption and separation of organic dyes - Gaikwad, Supriya Hanmant; Porel Mukherjee, Shatabdi (Environmental Science-Nano, 2022)
MoO3-x/N-doped-carbon (MoO3-x/N-C) nanocomposites with nanobelt structures were prepared by the in situ carbonization of the (NH4)Mo3O9-(NH4)(2)Mo4O13/oleylamine-oleic acid hybrids, and were designed using a two-step tailored nanoemulsion method followed by a solvothermal process. The MoO3-x/N-C nanocomposites possess high stability in a wide pH range of 1-11. In addition to the formation mechanism, detailed studies on adsorption properties, including adsorption isotherms, kinetics, mechanism, and reusability of the MoO3-x/N-C nanocomposites were systematically studied. The effects of various parameters on the adsorption characteristics, such as adsorbate concentration, contact time, pH, and temperature, were also evaluated. The detailed investigation of the kinetics and adsorption mechanism of MB from an aqueous solution showed that the adsorption process follows a pseudo-second-order kinetics and intraparticle diffusion model. The adsorption isotherm study demonstrated that the Langmuir isotherm model could illustrate the experimental data with a maximum adsorption capacity value of similar to 1360 mg g(-1), which turns out to be the highest among the previously reported adsorbents based on MoO3 nanomaterials, and is attributed to multiple adsorption mechanisms including electrostatic, pi-pi stacking, and H-bonding interactions between the MB dye and the MoO3-x/N-C nanocomposites. Thermodynamic analysis suggested that MB adsorption onto the MoO3-x/N-C nanocomposites was spontaneous and endothermic. Additionally, the adsorption and desorption cycles were examined for 100 ppm aqueous MB solution, where the removal efficiency by the MoO3-x/N-C nanocomposites remained at similar to 99% even after four regeneration cycles. Furthermore, the MoO3-x/N-C nanocomposites could selectively adsorb MB from a binary solution mixture containing two times higher concentrations of an anionic dye, methyl orange (MO), and the separation efficiency obtained was similar to 99% at neutral pH. More significantly, the MoO3-x/N-C nanocomposites could successfully and simultaneously adsorb several cationic dyes, including MB, malachite green (MG), crystal violet (CV), safranin O (SO), and separate an anionic dye, MO, from quaternary and pentanary dye mixture solutions with a separation efficiency of similar to 75% and 62%, respectively, at neutral pH. To the best of our knowledge, the effective separation of a single component by molybdenum oxide-based nanomaterials via a simple batch separation technique from a four/five-component mixed interfering analyte, close to a real matrix system, in an aqueous medium at neutral pH has not been reported so far. Therefore, the MoO3-x-based nanocomposite could be a new promising material for application in dye wastewater treatment.

Ligand-free one-pot synthesis of Ru/W18O49 self-assembled hierarchical coral-like nanostructures for selective conversion of glucose into glycols - Patil, Manoj Krishnat; Gaikwad, Supriya Hanmant; Kirali, Arun Arunima Balachandran; Marimuthu, Banu; Mukherjee, Shatabdi Porel (ACS Applied Nano Materials, 2023)
In this study, we report a simple inorganic route for the synthesis of Ru/W18O49 self-assembled coral-like nanostructures, with the following advantages: It is one step and requires no surfactant or stabilizing agent; Ru loading is easily tuned, and the as-synthesized nanomaterials can be used as a catalyst without any further processing. The preliminary investigations of the catalytic performance of these as-synthesized Ru/W18O49 nanomaterials appear quite promising for converting glucose to glycols. The total glycol selectivity of 82.6% with 100% conversion of glucose was obtained over 0.03 wt % Ru loading on tungsten nanostructures, which turns out to be the lowest Ru loading% on support reported to date to achieve the highest total glycol selectivity among the previously reported catalyst based on Ru-nano/composite materials. Additionally, preliminary results show that the concentration of Ru on W18O49 significantly affects the selectivity of the glycol production. Thus, our methodology will open up a wide range of opportunities regarding the choice of metals, stoichiometric/nonstoichiometric WOx (x=1-3) as support, and the viability of further catalytic manipulations. A probable catalytic mechanism for this catalytic process is also proposed.
Keywords: glycols; Nanostructure; One-pot synthesis; ruthenium (Ru); selective conversion of glucose; tungsten oxide (W18O49)